Metal–organic frameworks in proton-exchange membrane for intermediate-to-high-temperature fuel-cell applications: a review - Yong, Se Eh Noum; Min, Meng Pang; Wai, Yin Wong; Wu, Bo (Penerbit Universiti Kebangsaan Malaysia, 2023)
A proton-exchange membrane (PEM) is a vital component in fuel cells as a solid electrolyte that conducts ions. The high cost and degradation of Nafion® membrane in low-temperature fuel cells limits the technology’s commercialization. The development of intermediate (IT-PEMFCs) to high-temperature (HT-PEMFCs) fuel cells operating within the range of 80–200 °C has made progress over the last few decades, and improvements in water management addressing the issues of low-temperature PEMFCs have been observed. However, these types of PEM fuel cells (IT-PEMFCs and HT-PEMFCs) still face considerable challenges, such as unsatisfactory performance stability at high temperatures. Particularly, in HT-PEMFC, despite the high acid doping level (ADL) in membranes as a potential means to improve proton conductivity, high ADL decreases the membrane’s mechanical stability. Recently, metal–organic frameworks (MOFs) have achieved satisfactory results in applications of PEM modification. This manuscript reviews the development in applying MOFs in improving the properties of composite membranes in IT- and HT-PEMFCs by using SPEEK and PBI, respectively. The synthesis strategies using MOFs in the PEM are discussed together with the electrochemical properties obtained. The success of incorporating of MOFs into PEMs could shed light on the synthesis of new-generation IT- and HT-PEMFCs, which could improve several properties such as mechanical and thermal stability, oxidative stability, and acid-retention capacity.